Guinea : Request for Debt Relief Under the Catastrophe Containment Window of the Catastrophe Containment and Relief Trust-Staff Report; and Press Release. (IMF Staff Country Reports; Country Report ;, 2015)
This paper discusses Guinea's Request for Debt Relief Under the Catastrophe Containment (CC) Window of the Catastrophe Containment and Relief (CCR) Trust. Since early 2014, Guinea has been experiencing an ongoing Ebola epidemic that has spread to several countries in the region. The immediate economic effect of the Ebola epidemic has been a pronounced slowdown in 2014. Performance under the Extended Credit Facility arrangement has been satisfactory, the difficult macroeconomic environment notwithstanding. The IMF staff supports the authorities' request for assistance under the CC window of the CCR Trust given the nature of the public health disaster, and the ensuing financing needs to contain the disease and rehabilitate Guinea's public health system.